Diagnostic and therapeutic laparoscopy in assessment and management of patients with appendiceal neoplasms. (3rd April 2018) - Tan, Grace Hwei Ching; Shamji, Tushar; Mehta, Akash; Chandrakumaran, Kandiah; Dayal, Sanjeev; Mohamed, Faheez; Carr, Norman J.; Rowaiye, Babtunde; Cecil, Tom; Moran, Brendan J.
Abstract: Introduction: Radiological imaging often underestimates the extent of low volume peritoneal disease. The benefit of laparoscopy in assessing peritoneal metastases from colorectal and gastric cancer is accepted, but is inconclusive for appendiceal malignancy. We report our experience of diagnostic (DL) and therapeutic laparoscopy (TL) in patients with appendiceal tumours to determine indications and role in assessment and management. Methods: A retrospective review of a National Peritoneal Malignancy Centre's prospectively maintained database was performed. All patients with appendiceal neoplasms who underwent DL or TL between September 2011 and January 2016 were included. The indications and outcomes of the laparoscopy, complications and interval to laparotomy were evaluated. Results: Six hundred and eighty-five patients underwent surgery for appendiceal neoplasms during the study period, of which 73 (10.6%) underwent laparoscopy (50 DL, 23 TL). The main indications for DL were to clarify imaging and stage patients with high-risk histology. Indications for TL were an abnormal appendix without gross pseudomyxoma peritonei (PMP) or with low volume PMP, and concerns for fertility in the presence of PMP. DL resulted in 16 patients (32%) avoiding laparotomy because of extensive disease or no tumour found. Overall, 28 patients were assessed to have resectable disease and at laparotomy, 25/28 had complete cytoreduction with three patients unresectable. In the TL group, appendicectomy and peritoneal lavage was achieved in all four women with fertility concerns, allowing them to conceive thereafter. There were no complications. Conclusions: Patients with high-risk appendiceal neoplasm may benefit from DL, and potentially avoid unnecessary laparotomy. TL is useful in patients with low volume PMP and may aid fertility in selected patients.